Sosialisasi Produk Unggulan Desa Menuju One Village One Product Kabupaten Lombok Barat - Tajidan Tajidan; Bambang Dipokusumo; L. Sukardi; Fahrudin Fahrudin (Universitas Mataram, 2026)
In realizing the vision of prosperity from the village, the West Lombok Regency government pays attention to the development of superior village products into one village product. The socialization of village ungulan products into one village one product is a strategic step in an effort to involve the participation of all stakeholders in building superior village products that are independent and globally competitive. The purpose of socialization is: introducing superior village products; Agree on strategies and policies to improve the status of Ungulan Village products to One Village One Product. Socialization was carried out by applying the presentation method and Focus Group Discussion (FGD). The activity was guided by the moderator, observed and recorded by Nutulis. The results of the socialization activity are the introduction of superior product priorities developed as one village one product with alternative strategies to increase human resource creativity, utilize the potential of natural resources and the environment, apply environmentally friendly and digital technology, optimize local, regional, and international market opportunities; improvement of packaging quality, brand, and quality standards, disaster mitigation, risks and threats, preparation and standardization of standard operating procedures (SOP).